Factfulness: theoretical and empirical considerations within affect-related research in mathematics education - Amico, Andrea; Andrà, Chiara; Doria, Luca (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
The study aims to investigate the role of mathematical beliefs in the context of environmental and social issues, when people have to rate the incidence of certain phenomena. The framework of Factfulness is intertwined with mathematics-related beliefs and the emergence of conceptions is investigated. In this research, we asked a group of students in Environmental Sciences and a group of researchers in mathematics education a series of multiple-choice questions retrieved from the Factfulness website. The results reveal that mathematics- and/or environmental-knowledgeable people tend to be less pessimistic than the average population with respect to social and environmental facts such as pollution, cost of solar energy, people perceiving climate change as a threat, and the like.